2008
DOI: 10.1007/s00280-008-0757-z
|View full text |Cite
|
Sign up to set email alerts
|

Altered cyclophosphamide and thiotepa pharmacokinetics in a patient with moderate renal insufficiency

Abstract: Purpose We report a patient with renal insuYciency (creatinine clearance, CL cr = 38 mL/min) who received high-dose chemotherapy with cyclophosphamide (1,500 mg/m 2 day ¡1 ), thiotepa (120 mg/m 2 day ¡1 ) and carboplatin (AUC = 5 mg min/mL day ¡1 ) for four consecutive days. Methods Blood samples were collected on day 1 and 3 and plasma levels of cyclophosphamide, its active metabolite 4-hydroxycyclophosphamide, thiotepa, its main metabolite tepa and carboplatin were determined. Results Pharmacokinetic analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…However, the latter report also showed that renal insufficiency was associated with longer duration of fever and hospitalization, and seemed to be related to the adverse effects of melphalan . In a case report on the pharmacokinetics of thiotepa in a patient with renal insufficiency, the patient experienced excessive exposure to tepa, an active metabolite of thiotepa . Taken together, these findings suggest that it is reasonable to reduce doses of thiotepa and melphalan according to the patient's Ccr.…”
Section: Discussionmentioning
confidence: 93%
“…However, the latter report also showed that renal insufficiency was associated with longer duration of fever and hospitalization, and seemed to be related to the adverse effects of melphalan . In a case report on the pharmacokinetics of thiotepa in a patient with renal insufficiency, the patient experienced excessive exposure to tepa, an active metabolite of thiotepa . Taken together, these findings suggest that it is reasonable to reduce doses of thiotepa and melphalan according to the patient's Ccr.…”
Section: Discussionmentioning
confidence: 93%
“…2 There is a small amount of data which shows that renal impairment increases systemic drug exposure, but data does not demonstrate clinically relevant changes. 2,23,24 Before the drug is administered the severity of renal impairment should be considered. 2 Table 2 lists some drug-drug interactions with cyclophosphamide.…”
Section: Alterations To Metabolism and Eliminationmentioning
confidence: 99%
“…When renal function is compromised, drug and metabolites eliminated through the kidneys may accumulate to toxic levels with repeated dosing. 14 We report here on a 12-year-old boy with osteosarcoma undergoing chemotherapy with doxorubicin, cisplatin, methotrexate, ifosfamide, and etoposide. Renal elimination of doxorubicin accounts for only 5% to 15% and is therefore less important concerning renal impairment.…”
Section: Discussionmentioning
confidence: 98%